2023
DOI: 10.3384/9789180751315
|View full text |Cite
|
Sign up to set email alerts
|

Enterocutaneous fistula : Patients', families' and healthcare professionals' experiences - epidemiology and outcomes

Abstract: Introduction: Enterocutaneous fistula is a rare and complex condition with high morbidity.The condition causes multiple health problems, and it is both physically and psychologically demanding for the affected person and their families. Infection, fistula wound care challenges, electrolyte and fluid imbalance, and malnutrition render the individual in need of long periods of in-hospital care and homecare. This also places great demands on healthcare professionals and knowledge among healthcare professionals ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Several studies highlighted that fistula output remains increased despite administering loperamide, an antidiarrhoeic. The studies conducted by Shover and Todorow 30 and Ballard et al 45 confirmed that octreotide and lanreotide inhibit the effect of gastrointestinal juices and lessen fistula output 30,35,39 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Several studies highlighted that fistula output remains increased despite administering loperamide, an antidiarrhoeic. The studies conducted by Shover and Todorow 30 and Ballard et al 45 confirmed that octreotide and lanreotide inhibit the effect of gastrointestinal juices and lessen fistula output 30,35,39 …”
Section: Discussionmentioning
confidence: 93%
“…Parli et al 37 and Härle et al 38 both argued that opioid usage decreases gastric motility while somatostatin reduces gastric hormones 37,38 . Critical care nurses should provide emotional support by assisting the patients, ensuring comfort, and guiding them through their disease process 39 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations